The computational study of sand dune architecture – pre-simulation for sand forming with wind-directing robots. (18th December 2017) - Okawa, Haruna; Hotta, Kensuke; Ikeda, Yasushi
ABSTRACT: This paper examines the relationship between computer fluid dynamics and mass physics simulation in a desert-like space with obstacles. By using the result of these simulations, a shape and its behaviour of obstacles called 'wind-directing robots' are designed. Those shapes as well as behaviours make sand dune much controllable in order to realise a large-scale additive construction method. By utilising local materials and natural energy, in here sand and wind, as the main sources of power to form materials, the final outcome of this research enables us to increase the efficiency in future construction as well as create architectural ecosystems that consume less energy.